KHUL’ AL-ADILLAH: QIRĀ’AH NAḤWIYYAH JADĪDAH - Husein Mohammad; Mohammad Dakeel (Islam Futura, 2017)
Getting rid of Evidence is a common syntactic phenomenon in various syntactic sub-disciplines. This researcher attempted to investigate the locations of such phenomenon in the primary sources of the Arabic language. This research was conducted to shed light on this phenomenon with a new perspective that takes the following into consideration: 1) The concept of getting rid of evidence and the wide spreads in this semantic meaning with control; 2) The locations of this particular phenomenon; 3) The conditions for getting rid of evidence for the article; 4) The cases of getting rid of evidence and the reasons behind it; 5) The evidence is related to this particular phenomenon as it exists in the Holy Quran and Arabic poetry. The study was concluded with a summary of the major findings of the research. The researcher hopes that the findings of this study will benefit those scholars interested in the Arabic language.